2022
DOI: 10.3390/jintelligence10020029
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Wong and Law Emotional Intelligence Scale in a Colombian Manager Sample

Abstract: Within the organizational field, emotional intelligence is linked to socially competent behaviors, which allow the development of labor and organizational abilities necessary for professional development. Thus, in workers, emotional intelligence is related to a wide range of organizational variables. The purpose of the present study was to evaluate the psychometric properties of the Wong and Law Emotional Intelligence Scale (WLEIS) in the Colombian context, specifically, in a population of managers. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
2
6
0
1
Order By: Relevance
“…Contrary to Wong and Law's [ 28 ] original study which offered empirical support for a second-order factor model, the results suggested three lower-order factors (others-emotion appraisal, use of emotion and self-regulated emotion appraisal) that could not be adequately explained by a single broader dimension of emotional intelligence. The findings seem to corroborate empirical studies that question the presence of a reliable general emotional intelligence higher-order factor for the WLEIS and the variation in consistency of the four-factor factor structure across different population groups [ 29 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Contrary to Wong and Law's [ 28 ] original study which offered empirical support for a second-order factor model, the results suggested three lower-order factors (others-emotion appraisal, use of emotion and self-regulated emotion appraisal) that could not be adequately explained by a single broader dimension of emotional intelligence. The findings seem to corroborate empirical studies that question the presence of a reliable general emotional intelligence higher-order factor for the WLEIS and the variation in consistency of the four-factor factor structure across different population groups [ 29 ].…”
Section: Discussionsupporting
confidence: 82%
“…Although the convergent validity of this factor is questionable, this finding provides interesting insight into the self-regulated emotion appraisal of the young emerging adult. For this sample, having insight into one's feelings and controlling one's temper seem important for handling difficulties rationally [ 29 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited literature on happiness and EI relation in medical education made our work distinctive 4,45 . Moreover, it is noteworthy to mention that current research differs from previous projects regarding the use of BEIS‐10 as an EI indicator 25,46–48 and large sample size (multicenter methodology) 4,16,49 . Besides, more comparative detail will be elaborated between present and previous studies to clarify the study methodology and justification for conducting a similar project.…”
Section: Discussionmentioning
confidence: 87%
“…Es una prueba de ejecución típica que responde a una reformulación teórica del modelo de Mayer y Salovey (1997), diseñada específicamente para adultos, consta solo de 16 ítems y ha sido utilizada en ámbitos clínicos, educativos y organizacionales. Además, cuenta con estudios transculturales y ha sido adaptada a diversos contextos, como China, Japón, Corea del Sur, India, Italia (Rathore y Chadha, 2021;Acosta-Prado et al, 2022) y España (WLEIS-S; Extremera et al, 2019).…”
Section: Introductionunclassified